Coping with Chronic Warfare. The Athenian Experience - Carl Hampus Lyttkens; Henrik Gerding (Lund University, School of Economics and Management, Department of Economics, 2019)
In Classical Athens, being at war was much more common than peace. The military expenditures were correspondingly large. The real enigmatic issue, however, is not financial but where they found the manpower needed for this policy. The number of warships (triremes) was so great that there is no way that the citizen could have dominated in the crews. The main source is likely the non-citizen, free population of Attica. Slaves, one the other hand, would have been very popular as rowers during the final phase of the Peloponnesian war, but not necessarily before. The manpower losses in connection with naval conflicts must have had a significant impact on Athenian society in several ways. We discuss three examples: the switch from ostracism to the graphe paranomon, the new law on citizenship under Perikles, and why the Athenian Assembly put the victorious generals on trial after the victory at Arginoussai.
Keywords: N13; N43; N93; 330; Ancient Athens; slaves; rowers; war; demographic change